1977
DOI: 10.1021/bi00631a015
|View full text |Cite
|
Sign up to set email alerts
|

Substrate selectivity of squalene synthetase

Abstract: Six 1-3H-labeled analogues of farnesyl pyrophosphate have been studied as potential substrates for yeast and rat liver squalene synthetases: 2-methylfarnesyl pyrophosphate (4), 3-demethylfarnesyl pyrophosphate (5), 7,11-dimethyl-3-ethyl-2,6,10-dodecatrienyl pyrophosphate (6), 6,7,10,11-tetrahydrofarnesyl pyrophosphate (7), 4-methylthiofarnesyl pyrophosphate (8), and 4-fluorofarnesyl pyrophosphate (9). Analogues 4 and 5 are enzymatically incorporated into 11-methylsqualene (10) and 10-demethylsqualene (11), res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…CrtM was further engineered through mutations to accept C 25 farnesylgeranyl diphosphate, yielding C 40 , C 45 and C 50 homologues of dehydrosqualene in the presence of FPP, farnesylgeranyl diphosphate and GGPP 42 43 . In another study, SSs from yeast, pig and rat have been shown to accept non-natural derivatives of FPP, to generate several unnatural terpene products in vitro 45 46 . In addition, yeast SS has been shown to yield alternative products in vitro from FPP as a substrate under various non-physiological reaction conditions, such as in the absence of NADPH with extended incubation times or in the presence of an unreactive NADPH analogue 47 48 49 .…”
Section: Discussionmentioning
confidence: 99%
“…CrtM was further engineered through mutations to accept C 25 farnesylgeranyl diphosphate, yielding C 40 , C 45 and C 50 homologues of dehydrosqualene in the presence of FPP, farnesylgeranyl diphosphate and GGPP 42 43 . In another study, SSs from yeast, pig and rat have been shown to accept non-natural derivatives of FPP, to generate several unnatural terpene products in vitro 45 46 . In addition, yeast SS has been shown to yield alternative products in vitro from FPP as a substrate under various non-physiological reaction conditions, such as in the absence of NADPH with extended incubation times or in the presence of an unreactive NADPH analogue 47 48 49 .…”
Section: Discussionmentioning
confidence: 99%
“…The filtrate was concentrated to a volume of 3 mL and purified by MPLC on SP207SS gel (2.5 x 25 cm column), eluting with water followed by a gradient created by the gradual addition of 2-propanol to a reservoir of water. Product fractions were combined and concentrated, and the aqueous solution was lyophilized to give 302 mg (50%) of 7 as a white solid: IR (KBr) 2926, 1653, 1507, 1150, 1026, 926, 878 cm"1; NMR (D20) 6 7.73 (d, 2H, «7=8.1 Hz,), 7.68 (d, 2H, J = 6.8 Hz), 7.56 (t, 2H, «7 = 7.5 Hz), 7.48 (d, 2H, «7 = 8.1 Hz), 7.46 (t, 1H, «7 = 7.3 Hz), 2.75 (m, 2H), 1.93 (m, 4H), 1.68 (m, 1H), 1.40 (d, 3H, J = 13.7 Hz); 13C NMR 20) ó 143.32,140.58, 137.98, 129.47, 129.27, 127.60, 126.99, 126.91, 43.68 (dd, «7 = 83, 116 Hz), 35.59, 32.96 (t, «7 = 5.9 Hz), 26.59, 16.97 (d, «7 = 92 Hz); MS (FAB, + ions) m/z 391 ( + 2H -Na), 413 ( + H), 435 (M + Na), 457 ( -H + 2Na). Anal.…”
Section: Methodsmentioning
confidence: 99%
“…In the second half-reaction, thought to occur at a second catalytic site within the enzyme active center (6 -8), PSQPP undergoes heterolysis, isomerization, and reduction with NADPH to form squalene. It has been postulated that the SQS catalytic machinery consists of two nonidentical FPP binding sites (9,10), one that binds FPP in a conformation that facilitates its cleavage to yield an allylic carbocation, and one that binds FPP in an orientation that facilitates carbocation insertion into its C2-C3 double bond * The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked "advertisement" in accordance with 18 U.S.C.…”
mentioning
confidence: 99%